Efficacy of different doses and timing of tranexamic acid in major orthopedic surgeries: a randomized trial - Saravanan,Ravi (2020)
Abstract Background: Tranexamic acid was studied in four different dosage regimens and their efficacy was compared for perioperative blood loss reduction, blood transfusion requirements and deep vein thrombosis (DVT) complication. Methods: Two hundred patients undergoing major orthopedic procedures were divided into five groups containing 40 patients each: Placebo, low dose (bolus 10 mg kg-1), low dose + maintenance (bolus 10 mg kg-1 + maintenance 1 mg kg-1 hr-1), high dose (bolus 30 mg kg-1) and high dose + maintenance (bolus 30 mg kg-1 + maintenance 3 mg kg-1 hr-1). Surgical blood loss was measured intraoperatively and drains collection in the first 24 hours postoperatively. Blood transfusion was done when hematocrit falls less than 25%. DVT screening was done in the postoperative period. Results: The intraoperative blood loss was 440 ± 207.54 mL in the placebo group, 412.5 ± 208.21 mL in the low dose group, 290 ± 149.6 ml in the low dose plus maintenance group, 332.5 ± 162.33 mL in the high dose group and 240.7 ± 88.15 mL in the high dose maintenance group (p < 0.001). The reduction in postoperative blood loss in the drain for first 24 hours was 80 ± 44.44 mL in the placebo group, 89.88 ± 44.87 mL in the low dose group, 56.7 ± 29.12 mL in the low dose plus maintenance group, 77.9 ± 35.74 mL in the high dose group and 46.7 ± 19.9 mL in the high dose maintenance group (p < 0.001). DVT was not encountered in any patient. Conclusion: Tranexamic acid was most effective in reducing surgical blood loss and blood transfusion requirements in a low dose + maintenance group.